PENGARUH PENGGUNAAN MEDIA MANIPULATIF DALAM PEMBELAJARAN PROYEK TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI PADA ANAK USIA 5-6 TAHUN DI PAUD HARAPAN MANDIRI - Putri Puspitasari; Dorlince Simatupang (JURNAL TEMATIK, 2019)
The purpose of this study was to know the effect of the use of manipulative media in project learning on the ability to recognize geometric shapes in children aged 56 years at Paud Harapan Mandiri. This type of research is true experiments. Determination of class samples is done randomly with a total sample of 15 classes per class. The instrument of data collection is the observation guide. Data analysis using t-test and observations were carried out with the observation guide that has been provided with a real level of α = 0.05. Based on the results of the study obtained an average value in the experimental class 10.73 with the highest value of 12 and the lowest value of 9, so that the ability of children to recognize the geometrical shape of the experimental class gained a significant difference. While the average value in the control class 6.7 with the highest value of 8 and the lowest value of 5, so that the ability of children to recognize the geometric shape of the control class has not been maximally developed. Based on these results the hypothesis states that tcount (10.58)> 〖t〗 _table (1,701) at the level of α = 0.05. So it can be concluded that the use of manipulative media in learning projects significantly influences the ability to recognize geometric shapes in children aged 5-6 years in Harapan Mandiri PAUD Medan District Medan City.